Educational Empowerment Through Ict Among Rural Women in The Chengalpattu District of Tamil Nadu: Challenges in Using Information and Communication Technology - D. Mehernissa, Dr. S.Thanikasalam (Journal of Neonatal Surgery, 2025)
The study investigates educational empowerment among rural women through Information and Communication Technology (ICT) and challenges in using ICT in Chengalpattu District, Tamil Nadu. Using a descriptive research design, data were collected from 255 rural women through a structured interview schedule, selected using a multistage sampling technique. The study assesses ICT usage, empowerment levels, and challenges faced by rural women. Findings indicate that rural women perceive the greatest educational empowerment through staying updated with current affairs (mean = 4.51), increased accessibility to learning (mean = 4.50), and supporting children's education (mean = 4.49). Age, marital status, occupation, income, and family type significantly influence empowerment, while educational qualifications do not. K-Means cluster analysis reveals 50% of women report high empowerment (mean = 4.39), while 58.33% face high-level ICT challenges (mean = 4.26) due to financial barriers, technical hurdles, and social stigma. The study recommends targeted digital literacy programs, financial assistance for ICT access, and community-based ICT initiatives to reduce barriers and enhance the educational empowerment of rural women. The research highlights the transformative potential of ICT in bridging educational and socio-economic gaps in rural communities.